2013
DOI: 10.1007/s00784-013-0971-x
|View full text |Cite
|
Sign up to set email alerts
|

Can preoperative imaging help to predict postoperative outcome after wisdom tooth removal? A randomized controlled trial using panoramic radiography versus cone-beam CT

Abstract: For management of postoperative complications for moderate-risk cases of impacted mandibular third molars, careful preoperative radiographic planning followed by an atraumatic surgical approach seems to be valuable, irrespective of the 2D or 3D nature of the preoperative images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 32 publications
5
70
0
10
Order By: Relevance
“…One study found that in 256 operated patients, 2 in the CBCT group and 5 in the PAN imaging group experienced permanent sensory disturbances to the IAN. 64 Moreover, in an ongoing study, preliminary results were that 17 of 116 operated patients had temporary neurosensory disturbances arising from the IAN. The distribution was 11 incidents in the CBCT group and 6 incidents in the PAN imaging group.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 97%
“…One study found that in 256 operated patients, 2 in the CBCT group and 5 in the PAN imaging group experienced permanent sensory disturbances to the IAN. 64 Moreover, in an ongoing study, preliminary results were that 17 of 116 operated patients had temporary neurosensory disturbances arising from the IAN. The distribution was 11 incidents in the CBCT group and 6 incidents in the PAN imaging group.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 97%
“…Risk of inferior alveolar nerve injury is associated with anatomic relationship between nerve and the tooth; Smith AC et al, [9] determined in their study that panoramic radiography is the slandered radiological examination to evaluate the anatomic relationship of third molar and inferior alveolar nerve. Guerrero ME et al, [14,15] found that even cone beam computed tomography was not superior to panoramic radiography in predicting post-operative sensory disturbances. Szalma J, et al, [10] in their study concluded that there is no significant advantage of digital panoramic radiography over conventional one.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies at the higher levels of hierarchy of diagnostic efficacy in accordance with Fryback and Thornbury 1 , to the authors' knowledge at the time of conducting this review, with only one randomized controlled trial having been published on the impact of CBCT on patient outcomes. 46 The many CBCT machines on the market have different image quality and the diagnostic capability of any machine will vary depending upon mode of operation. Thus, it might be argued that we will never be able to develop "definitive" guidelines with high grading of supporting evidence for CBCT.…”
Section: Discussionmentioning
confidence: 99%